Three-dimensional porous silicon and carbon nanosphere structure material taking lithium nitrate as template and lithium supplement agent, preparation method of three-dimensional porous silicon and carbon nanosphere structure material, lithium ion battery negative electrode and battery

A three-dimensional porous silicon@carbon nanosphere structure material using lithium nitrate as a template and lithium supplement addresses the issues of volume expansion and poor cycle stability in silicon-based materials, enhancing the electrochemical performance and cycle life of lithium-ion batteries.

CN119133388AActive Publication Date: 2024-12-13ANHUI NORMAL UNIV +1

Patent Information

Application Number
CN202411208722.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Existing lithium-ion batteries face challenges with silicon-based anodes that silicon-based materials face issues with silicon-based materials that silicon-based materials that silicon-based materials that silicon-based materials that silicon-based materials that silicon-based anodes that existing technologies have not effectively address the issues of volume expansion and poor cycle stability of silicon-based materials that silicon-based materials that existing technologies have not effectively addressed the issues of volume expansion and poor cycle stability of silicon-based materials as negative electrode materials in lithium-ion batteries.

Method used

A three-dimensional porous silicon@carbon nanosphere structure material is prepared using lithium nitrate as a template and lithium supplement, synthesized through a method involving the magnesium thermal reduction of SiO2 small spheres, followed by a template method to form a porous Si@C nanosphere structure, which alleviates volume expansion and enhances cycle stability.

Benefits of technology

The method results in a material with a high specific surface area and active sites, providing improved electrochemical performance and cycle life by buffering the volume change of silicon during lithium insertion and extraction, and acting as a lithium supplement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133388A_ABST
    Figure CN119133388A_ABST
Patent Text Reader

Abstract

The invention provides a three-dimensional porous silicon and carbon nanosphere structure material with lithium nitrate as a template and a lithium supplement agent, a preparation method of the three-dimensional porous silicon and carbon nanosphere structure material, a lithium ion battery negative electrode and a battery. Compared with the prior art, ethanol, deionized water, ammonia water and tetraethyl silicate are used for synthesizing SiO2 spheres, the SiO2 spheres are subjected to thermal reduction through magnesium powder to obtain porous Si, and the porous Si and carbon nanosphere structure material is used for preparing the lithium ion battery negative electrode. Dispersing the porous Si nanospheres and tris (hydroxymethyl) aminomethane in water; and adjusting the pH value by using a hydrochloric acid solution, continuously adding dopamine hydrochloride, finally adding lithium nitrate, calcining, washing and drying to obtain the Si-C composite material with the three-dimensional porous structure. A porous structure is further formed on the surface of the carbon layer by a template method, so that the composite material can provide more active sites in the charge-discharge process, and the porous structure effectively relieves the problem of volume expansion; and meanwhile, the added lithium nitrate also serves as a lithium supplement agent, and the supplemented lithium ions enable the battery to have better stability in the charging and discharging process of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery silicon negative electrode materials, and specifically relates to a three-dimensional porous silicon@carbon nanosphere structure material with lithium nitrate as a template and a lithium supplement agent, a preparation method thereof, a lithium ion battery negative electrode and a battery. Background Art

[0002] Due to the depletion of fossil fuels and the increasing environmental pollution, rechargeable lithium-ion batteries have attracted widespread attention due to their long cycle life and high energy density. They can be used in various applications such as portable electronics, electric vehicles and renewable energy storage. Silicon has a low lithium absorption potential and a high theoretical capacity, making it a very promising negative electrode material for the next generation of lithium-ion batteries.

[0003] However, silicon as anode material usually undergoes large volume changes during Li alloying and dealloying, resulting in severe pulverization of active materials and continuous formation of unstable solid electrolyte interfaces, which leads to rapid capacity decay of silicon anode during cycling, limiting its practical application.

[0004] The patent with the publication number CN 108336311 A published on July 27, 2018 discloses a method for preparing a silicon-carbon negative electrode material doped with silver particles. After the preparation of silicon slurry, the preparation of dopamine-coated silicon-carbon material, the preparation of precursor powder and heat treatment steps, the preparation of the silicon-carbon negative electrode material doped with silver particles is completed; dopamine is used as the carbon source for coating the silicon-carbon material, the pH of the solution is adjusted by trishydroxymethylaminomethane, dopamine self-polymerizes into polydopamine in an alkaline solution, and is coated on the surface of the silicon-carbon material, the coating effect is uniform, and the thickness of the carbon coating layer can be accurately controlled by adjusting the amount of dopamine, so as to achieve the best coating effect through optimization, the carbon coating layer can effectively alleviate the volume expansion of nano-silicon, and the reducibility of dopamine is utilized to dope metallic silver particles outside the coating layer, improve the conductivity of the material, reduce the electrode polarization, and make the material have good cycle performance and rate performance. However, according to the records in its embodiments, its first charge capacity is low, and the first efficiency and cycle performance are poor. Summary of the invention

[0005] The purpose of the present invention is to provide a three-dimensional porous silicon@carbon nanosphere structure material with lithium nitrate as a template and a lithium supplement agent and a preparation method thereof, wherein SiO2 small spheres are prepared using low-cost raw materials, porous Si is obtained by magnesium thermal reduction method, and a three-dimensional Si@C nanosphere structure material with lithium nitrate as a template and a lithium supplement agent is obtained after calcination, washing and drying by template method. The present invention provides a preparation method of nanomaterials with low cost, high yield and novel structure as a solution to the technical difficulties such as easy volume expansion and poor cycle stability of silicon-based materials as electrode materials.

[0006] Another object of the present invention is to provide a lithium ion battery negative electrode, which is prepared using the above-mentioned three-dimensional porous silicon@carbon nanosphere structure material.

[0007] The last object of the present invention is to provide a lithium ion battery prepared by using the above-mentioned lithium ion battery negative electrode, so as to solve the technical difficulties such as easy volume expansion and poor cycle stability of electrode materials.

[0008] The specific technical solutions of the present invention are as follows:

[0009] A method for preparing a three-dimensional porous silicon@carbon nanosphere structure material using lithium nitrate as a template and a lithium supplement, specifically comprising:

[0010] 1) Under magnetic stirring, porous Si nanospheres and tris(hydroxymethyl)aminomethane are dispersed in water, and the pH is adjusted with hydrochloric acid solution, dopamine hydrochloride is continuously added, and finally lithium nitrate is added for reaction;

[0011] 2) calcining the product of step 1) in a protective atmosphere, washing and drying, and obtaining a three-dimensional porous Si@C nanosphere structure material.

[0012] In step 1), the amount ratio of porous Si nanospheres to water is 0.001-0.004 g / mL, preferably 0.002 g / mL; the amount ratio of tris(hydroxymethyl)aminomethane to water is 0.15-0.25 mol / L, the pH is adjusted to 8-9 with hydrochloric acid solution, the amount ratio of dopamine hydrochloride to water is 0.005-0.007 mol / L, and the template method is used. Considering the battery performance, the amount ratio of lithium nitrate to water is 0.05-0.07 mol / L; preferably: the amount ratio of tris(hydroxymethyl)aminomethane to water is 0.2 mol / L, the pH is adjusted to 8.5, the amount ratio of dopamine hydrochloride to water is 0.006 mol / L, and the amount ratio of lithium nitrate to water is 0.06 mol / L;

[0013] In step 1), the reaction time is 20-30 hours, preferably 24 hours, and the reaction temperature is room temperature;

[0014] The preparation method of porous Si nanospheres in step 1) is:

[0015] 1-1) ethanol, deionized water and ammonia water are mixed, stirred, tetraethyl silicate is added dropwise, stirring is continued, the mixture is allowed to stand, the product is centrifuged and washed, and dried to obtain SiO2;

[0016] 1-2) SiO2, Mg powder and NaCl are mixed and ground, and then calcined. After the calcination, the mixture is soaked in HCl solution, washed alternately with HCl solution and deionized water, and dried to obtain porous Si balls;

[0017] Furthermore, in step 1-1), the volume ratio of ethanol, ammonia water, tetraethyl silicate and deionized water is 9:1.5:1:3 to 130:3.5:3:21; preferably, the volume ratio of ethanol, ammonia water, tetraethyl silicate and deionized water is 30:1.5:1:6; the mass concentration of ammonia water is 25%;

[0018] In step 1-1), the stirring time is 30mi-60min, the stirring time is continued for 0.5-2h, and the standing time is 5-10h, preferably the stirring is continued for 1h and the standing time is 10h; all are carried out at room temperature;

[0019] The size of the SiO2 particles prepared in step 1-1) is 200 to 800 nm; preferably 200 to 500 nm;

[0020] In step 1-2), the mass ratio of SiO2, Mg powder and NaCl is 1:1:10 to 1:1.2:30, and the preferred mass ratio is 1:1:20;

[0021] In step 1-2), the calcination conditions are: calcination in a hydrogen-argon mixed gas atmosphere at 600-750° C. for 4-8 hours; preferably, the calcination conditions are 650° C. for 6 hours; in the hydrogen-argon mixed gas, the volume fraction of hydrogen gas is 5%, and the volume fraction of argon gas is 95%;

[0022] In step 1-2), after calcination, the sample is soaked in HCl solution, and finally washed alternately with HCl solution and deionized water, and dried in an oven to obtain porous Si balls; the concentration of the HCl solution is 3 to 5M, and the soaking time is 3 to 10 hours, preferably the concentration of the HCl solution is 3M, and the soaking time is 5 hours.

[0023] The protective atmosphere in step 2) refers to a nitrogen atmosphere;

[0024] The calcination in step 2) is carried out by increasing the temperature to 550±30° C. at a heating rate of 2° C. / min and calcining for 2±0.2 h to obtain a three-dimensional porous Si@C nanosphere structure material.

[0025] The washing and drying in step 2) refers to washing with water, washing three times, and then drying in an oven at 60° C. for 12 hours.

[0026] In the preparation method of the present invention, the silicon sphere itself is a three-dimensional structure, which is subjected to magnesium thermal reduction: first, Mg vapor reacts with SiO2 to generate Si crystals and MgO solids, followed by hydrochloric acid immersion, and HCl etching to remove MgO, and finally a Si porous structure is formed. After lithium nitrate is subsequently added, lithium nitrate is used as a template, and the lithium nitrate template is easily dissolved in water and washed away, forming pores on the surface of the carbon layer, thereby forming a unique three-dimensional porous structure.

[0027] The present invention uses ethanol, deionized water, tetraethyl silicate and ammonia water to synthesize SiO2 small balls, and obtains porous Si by thermal reduction of SiO2 with magnesium powder, and then calcines it in a tube furnace to convert it into a Si@C composite material with a three-dimensional porous structure. The porous structure can not only increase the specific surface area, but also effectively alleviate the volume expansion of silicon particles. At the same time, the introduction of lithium nitrate allows a small amount of lithium ions to be adsorbed on the surface of the nanomaterial, acting as a lithium supplement, thereby further improving the electrochemical performance of the battery.

[0028] The invention provides a three-dimensional porous silicon@carbon nanosphere structure material with lithium nitrate as a template and a lithium supplement, which is prepared by the above method, has a size of 200-500nm, a core of porous Si, a shell of a carbon layer, pore sizes distributed in the core and the shell, and lithium nitrate as a template for pore formation.

[0029] The present invention provides a lithium-ion battery negative electrode, which is prepared using the above three-dimensional porous silicon@carbon nanosphere structure material as an active material. The specific preparation method is:

[0030] The three-dimensional porous silicon@carbon nanosphere structure material is mixed with a conductive agent and a binder, and then ground to obtain a slurry, which is then coated on a copper foil and dried to obtain a three-dimensional porous structure composite material, which is used as a negative electrode for a lithium-ion battery to make a lithium-ion battery.

[0031] The mass ratio of the three-dimensional porous silicon@carbon nanosphere structure material to the conductive agent and the binder is 7:2:1;

[0032] The conductive agent is conductive carbon black; the binder is polyvinylidene fluoride;

[0033] The film drawing conditions are carried out on copper foil, the drying conditions are 60-80°C, and the time is 20-24 hours.

[0034] The film is coated on copper foil, dried at 60-80°C for 20-24 hours, and cut into small discs to obtain a three-dimensional porous Si@C composite material as a negative electrode for lithium-ion batteries.

[0035] The present invention provides a lithium ion battery, which is prepared using the above-mentioned lithium ion battery negative electrode. The specific method of assembling the battery is:

[0036] A lithium-ion battery was assembled in a glove box using a lithium sheet as a counter electrode and a lithium carbonate negative electrode as a negative electrode. The electrolyte was a solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and the solute was LiPF6.

[0037] In the preparation method based on the three-dimensional porous Si@C nano-spherical structure material provided by the present invention, ethanol, deionized water and ammonia water are used to synthesize SiO2 small balls, and the SiO2 small balls are thermally reduced by magnesium powder at 600-750°C to obtain porous Si, and finally calcined at 550±30°C, washed and dried to obtain a three-dimensional porous Si@C composite material. Lithium nitrate is used as a template, and after being dissolved in water, a porous structure is further formed on the surface of the carbon layer, so that the composite material can provide more active sites during the charge and discharge process. The porous structure effectively alleviates the problem of volume expansion. At the same time, the residual lithium ions after cleaning act as a lithium supplement. During the charge and discharge process of the battery, the supplemented lithium ions make the battery have better stability.

[0038] The present invention mixes low-cost ethanol, deionized water, tetraethyl silicate and ammonia water to synthesize SiO2 pellets, which greatly reduces the experimental cost. At the same time, the obtained SiO2 pellets are thermally reduced to porous silicon in the presence of magnesium powder and NaCl. NaCl is used as a heat sink to prevent silicon nanoparticles from melting and agglomerating due to high temperature while maintaining the integrity of the porous structure. The porous silicon nanoparticles are wrapped with a thin carbon shell, which forms a three-dimensional omnidirectional conductive network with the internal porous structure, providing a fast diffusion electron transfer channel, thereby promoting the electrode reaction kinetics. At the same time, the external carbon shell provides protection for the silicon nanoparticles, buffers the internal voids of the material, and alleviates the Li + The huge volume change of the material during the insertion / extraction process ensures the integrity of the electrode structure and can greatly improve the cycle life of the battery.

[0039] During the charge and discharge process of Si@C batteries, the serious volume expansion of silicon and the repeated destruction and reconstruction of the SEI film will lead to rapid capacity decay. Nano-sizing the composite material and rationally designing the spatial structure of the composite material can effectively increase its specific surface area and active sites. At the same time, adding lithium nitrate can also relatively reduce the loss of lithium ions in the active material, thereby alleviating the decay of the battery capacity. In the present invention, porous silicon particles are synthesized, a carbon layer is grown on the surface, and lithium nitrate is added. The lithium nitrate not only acts as a reaction template, but also supplements the lithium ions in the reaction process, effectively improving the capacity and cycle life of the battery.

[0040] Compared with the prior art, the present invention has the following advantages: the Si@C nanomaterial prepared by the magnesium thermal reduction method and the template method can well maintain a three-dimensional porous spherical structure, can provide a large specific surface area and more active sites, and the porous structure can well inhibit the volume expansion of silicon; the prepared Si@C nanocomposite material has stable chemical properties, is not easily oxidized in the air, and is easy to store; Li +There is a significant difference in the volume of silicon before and after insertion / extraction, resulting in a rapid decrease in capacity, while the carbon matrix shortens the path of electrons / ions and alleviates the strain of volume change; lithium nitrate acts as a template and lithium supplement, which can effectively improve the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a SEM image of the SiO2 nanospheres prepared in Example 1;

[0042] Figure 2 This is the SEM image of the porous Si spheres prepared in Example 1;

[0043] Figure 3 TEM image of the porous Si sphere prepared in Example 1;

[0044] Figure 4 This is a SEM image of the three-dimensional porous Si@C nanospheres prepared in Example 1;

[0045] Figure 5 TEM image of the three-dimensional porous Si@C nanospheres prepared in Example 1;

[0046] Figure 6 XRD pattern of the three-dimensional porous Si@C nanospheres prepared in Example 1;

[0047] Figure 7 This is a SEM image of SiO2 nanospheres prepared in Example 2;

[0048] Figure 8 This is a SEM image of the three-dimensional porous Si@C nanospheres prepared in Example 2;

[0049] Fig. 9 This is a SEM image of the three-dimensional porous Si@C nanospheres prepared in Example 3;

[0050] Fig.10 TEM image of the porous Si spheres prepared in Example 4;

[0051] Fig.11 This is a SEM image of the three-dimensional porous Si@C nanospheres prepared in Example 4;

[0052] Fig.12 This is a SEM image of the three-dimensional porous Si@C nanospheres prepared in Example 5;

[0053] Fig.13 This is a SEM image of the three-dimensional porous Si@C nanospheres prepared in Example 7;

[0054] Fig.14 TEM image of the three-dimensional porous Si@C nanospheres prepared in Example 8;

[0055] Fig.15 TEM image of the three-dimensional porous Si@C nanospheres prepared in Example 9;

[0056] Fig.16 TEM image of the three-dimensional porous Si@C-0.6 nanospheres prepared in Example 10;

[0057] Fig.17 The three-dimensional porous Si@C nanomaterial prepared in Example 1 is used as the negative electrode of lithium-ion battery at 0.1Ag -1 Charge and discharge curves under current density;

[0058] Fig.18 The three-dimensional porous Si@C nanomaterial prepared in Example 1 is used as the negative electrode of lithium-ion battery at 0.1Ag -1 Cycling performance diagram under current density;

[0059] Fig.19 The three-dimensional porous Si@C nanomaterial prepared in Example 1 is used as the negative electrode of lithium-ion battery at 0.5Ag -1 Charge and discharge curves under current density;

[0060] Fig. 20 The three-dimensional porous Si@C nanomaterial prepared in Example 1 is used as the negative electrode of lithium-ion battery at 0.5Ag -1 Cycling performance diagram under current density;

[0061] Fig.21 The three-dimensional porous Si@C nanomaterial prepared in Example 1 is used as the negative electrode of lithium-ion battery at 0.1-0.5A g -1 Rate performance diagram under current density;

[0062] Fig. 22 The three-dimensional porous Si@C nanomaterial prepared in Example 2 is used as the negative electrode of lithium-ion battery at 0.1Ag -1 Cycling performance diagram under current density;

[0063] Fig.23 The three-dimensional porous Si@C nanomaterial prepared in Example 3 is used as the negative electrode of lithium-ion battery at 0.1Ag -1 Cycling performance diagram under current density;

[0064] Fig.24 The three-dimensional porous Si@C nanomaterial prepared in Example 4 is used as the negative electrode of lithium-ion battery at 0.1Ag -1 Cycling performance diagram under current density;

[0065] Fig.25The three-dimensional porous Si@C nanomaterial prepared in Example 5 is used as the negative electrode of lithium-ion battery at 0.1Ag -1 Cycling performance diagram under current density;

[0066] Fig.26 The three-dimensional core-shell structure Si@C nanomaterial prepared in Example 6 is used as the negative electrode of lithium-ion battery at 0.1Ag -1 Cycling performance diagram under current density;

[0067] Fig. 27 The Si particles purchased from Aladdin in Example 7 were used as the negative electrode of lithium-ion batteries at 0.1A g -1 Cycling performance diagram under current density;

[0068] Fig.28 The three-dimensional core-shell structure Si@C / Li2CO3 nanomaterial prepared in Example 8 is used as the negative electrode of lithium-ion battery at 0.1A g -1 Cycling performance diagram under current density;

[0069] Fig.29 The three-dimensional core-shell structure Si@C / LiCl nanomaterial prepared in Example 9 is used as the negative electrode of lithium-ion battery at 0.1A g -1 Cycling performance diagram under current density;

[0070] Fig.30 The three-dimensional core-shell structure Si@C-0.6 nanomaterial prepared in Example 10 was used as the negative electrode of lithium-ion battery at 0.1A g -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION

[0071] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0072] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0073] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0074] Example 1

[0075] A method for preparing a three-dimensional porous silicon@carbon nanosphere structure material using lithium nitrate as a template and a lithium supplement, comprising the following steps:

[0076] 1) Preparation of SiO2 pellets

[0077] Mix 40 mL of ethanol, 8 mL of deionized water, and 2 mL of 25% ammonia water, stir magnetically for 30 minutes, then drop 1.6 mL of tetraethyl silicate and continue stirring for 1 hour. Let stand for 10 hours, collect the sample, wash it by centrifugation, and dry it in an oven at 60°C. The SEM image is shown below. Figure 1 As shown in the figure, it can be seen that it is a micro-nano sphere with a size of 200 to 500 nm.

[0078] 2) Preparation of porous Si spheres

[0079] The synthesized SiO2 pellets were subjected to the thermal reduction method of magnesium powder, specifically 0.1g SiO2, 0.1g Mg powder and 2.0g NaCl, mixed and ground for 10 minutes, and then placed in a hydrogen-argon mixed gas atmosphere with a hydrogen volume fraction of 5% and an argon volume fraction of 95%. The temperature was raised to 650°C at a heating rate of 5°C / min and calcined for 6 hours. After the calcination, the sample was soaked in a 3M HCl solution for 5 hours, and finally washed alternately with HCl solution and deionized water for 3 times, and the sample was dried in an oven at 60°C to obtain porous Si pellets. Its SEM picture is shown in Figure 2 As shown in the TEM image Figure 3 As shown in the figure, it can be seen that it is a porous structure with a size of 200 to 500 nm.

[0080] 3) Preparation of porous Si@C

[0081] Take 0.1g of the prepared porous silicon spheres, disperse them in 50mL of deionized water, and ultrasonicate for 10 minutes; under magnetic stirring, add 1.21g of tris(hydroxymethyl)aminomethane) to the solution; then adjust the pH to 8.5 with 12mol / L hydrochloric acid solution, continue to add 60mg of dopamine hydrochloride, and finally add 0.2g of lithium nitrate, and react at room temperature for 24h. Collect the composite material, wash it with deionized water and ethanol, and dry the sample in an oven at 60℃. The dried nanomaterials are heated to 550℃ at a heating rate of 2℃ / min, calcined in a nitrogen atmosphere for 2h, and finally washed with deionized water 3 times, and dried in an oven at 60℃ for 12h to obtain porous Si@C. Its SEM picture is shown as follows Figure 4 As shown in the figure, it can be seen that it is a spherical structure gathered together. Figure 5 shown.

[0082] The XRD pattern of the Si@C composite material obtained in this embodiment is shown in Figure 6 As shown, it is proved that the obtained product is Si@C.

[0083] Example 2 (for comparison)

[0084] A method for preparing a three-dimensional porous silicon@carbon nanosphere structure material using lithium nitrate as a template and a lithium supplement, comprising the following steps:

[0085] 1) Preparation of SiO2 pellets

[0086] Mix 40 mL of ethanol, 8 mL of deionized water, and 2 mL of 25% ammonia water. After magnetic stirring for 30 minutes, add 1.6 mL of tetraethyl silicate and continue stirring for 2 hours. Let stand for 15 hours, collect the sample, clean it by centrifugation, and dry it in an oven at 60°C. The SEM image is shown below. Figure 7 As shown in the figure, it can be seen that it is a micro-nano sphere with a size of 400 to 800 nm.

[0087] 2) Preparation of porous Si is the same as in Example 1;

[0088] 3) The preparation of porous Si@C is the same as in Example 1.

[0089] Its SEM picture is as follows Figure 8 As shown in the figure, it can be seen that it is a nanosphere of uniform size, with a size of 400 to 800 nm.

[0090] Figure 7 It can be seen that when synthesizing SiO2 beads in Example 2, as the reaction time increases, the size of SiO2 grows larger and is evenly and densely stacked together.

[0091] Example 3 (for comparison)

[0092] A method for preparing a three-dimensional porous silicon@carbon nanosphere structure material using lithium nitrate as a template and a lithium supplement, comprising the following steps:

[0093] 1) The preparation of the precursor is the same as in Example 1;

[0094] 2) Preparation of porous Si spheres:

[0095] The synthesized SiO2 pellets were prepared by thermal reduction of magnesium powder, specifically 0.1g SiO2, 0.08g Mg powder and 2.0g NaCl, mixed and ground for 10min, and then placed in a hydrogen-argon mixed gas atmosphere, heated to 600℃ at a rate of 5℃ / min and calcined for 8h. After calcination, the sample was soaked in 3M HCl solution for 5h, and finally washed alternately with HCl solution and deionized water for 3 times, and dried in an oven at 60℃ to obtain porous Si pellets.

[0096] 3) The preparation of porous Si@C is the same as in Example 1.

[0097] Its SEM picture is as follows Fig. 9 As shown, it can be seen from the figure that it is a uniform nanosphere structure.

[0098] During the magnesium thermal reduction process, when the proportion of magnesium powder is reduced, the excess SiO2 cannot be completely reduced to Si particles, and a large amount of white powder SiO2 will be on the surface of the final product Si@C, and MgO will be generated at the same time. When treated with hydrochloric acid, the excess SiO2 will not react, which results in the final product being porous Si and SiO2, resulting in rapid battery performance degradation and poor cycle stability.

[0099] Example 4 (for comparison)

[0100] A method for preparing a three-dimensional porous silicon@carbon nanosphere structure material using lithium nitrate as a template and a lithium supplement, comprising the following steps:

[0101] 1) The preparation of the precursor is the same as in Example 1;

[0102] 2) Preparation of porous Si spheres:

[0103] The synthesized SiO2 balls were subjected to the thermal reduction method of magnesium powder. Specifically, 0.1g of SiO2, 0.1g of Mg powder and 2.0g of NaCl were mixed and ground for 10 minutes, and then placed in a hydrogen-argon mixed gas atmosphere and heated to 650°C at a rate of 5°C / min for calcination for 6 hours. After calcination, the sample was soaked in 1M HCl solution for 5 hours, and finally washed alternately with HCl solution and deionized water for 3 times, and the sample was dried in an oven at 60°C to obtain porous Si balls. Its TEM image is shown in the figure below. Fig.10 As shown in the figure, it can be seen that it is a porous micro-nanosphere with a size of 200-500nm. After reducing the concentration of the HCl solution, it can be seen from the TEM image that the porous structure on the surface of the nanosphere is not obvious, which makes it easier to expand the volume during the charge and discharge process.

[0104] 3) Preparation of porous Si@C is the same as in Example 1

[0105] Its SEM picture is as follows Fig.11 As shown, it can be seen from the figure that it is a nanosphere structure with uniform size.

[0106] Example 5 (for comparison)

[0107] A method for preparing a three-dimensional porous silicon@carbon nanosphere structure material using lithium nitrate as a template and a lithium supplement, comprising the following steps:

[0108] 1) The preparation of the precursor is the same as in Example 1;

[0109] 2) The preparation of porous Si spheres is the same as in Example 1;

[0110] 3) Preparation of porous Si@C

[0111] Take 0.1 g of the porous silicon spheres prepared in step 2), disperse them in 50 mL of deionized water, and ultrasonicate for 10 minutes; under magnetic stirring, add 1.8 g of tris(hydroxymethyl)aminomethane) to the solution; then adjust the pH to 8.5 with hydrochloric acid solution, continue to add 90 mg of dopamine hydrochloride, and finally add 0.2 g of lithium nitrate, and react at room temperature for 24 hours. Collect the composite material, wash it with deionized water and ethanol, and dry the sample in an oven at 60°C. After drying, the nanomaterial is heated to 550°C at a rate of 2°C / min and calcined in a nitrogen atmosphere for 2 hours. Finally, it is washed 3 times with deionized water and dried in an oven at 60°C for 12 hours to obtain porous Si@C. Its SEM picture is as follows Fig.12 As shown in the figure, it can be seen that it is a spherical structure with a thick carbon layer and aggregated together, with a size of 200 to 500 nm.

[0112] Example 6 (for comparison)

[0113] A method for preparing porous Si@C comprises the following steps:

[0114] 1) The preparation of the precursor is the same as in Example 1;

[0115] 2) The preparation of porous Si spheres is the same as in Example 1;

[0116] 3) Preparation of porous Si@C

[0117] Take 0.1g of porous silicon spheres prepared in step 2), disperse them in 50mL of deionized water, and ultrasonicate for 10min; add 1.21g of tris(hydroxymethyl)aminomethane to the solution under magnetic stirring; then adjust the pH to 8.5 with hydrochloric acid solution, continue to add 60mg of dopamine hydrochloride, and react at room temperature for 24h. Collect the composite material, wash it with deionized water and ethanol, and dry the sample in an oven at 60℃. After drying, the nanomaterial is heated to 550℃ at a heating rate of 2℃ / min, and calcined in a nitrogen atmosphere for 2h to finally obtain porous Si@C.

[0118] Example 7 (for comparison)

[0119] A method for preparing silicon@carbon using lithium nitrate as a template and a lithium supplementing agent comprises the following steps:

[0120] Take 0.1g of Si beads purchased from Aladdin, disperse it in 50mL of deionized water, and ultrasonicate for 10 minutes; under magnetic stirring, add 1.21g of tris(hydroxymethyl)aminomethane) to the solution; then adjust the pH to 8.5 with hydrochloric acid solution, continue to add 60mg of dopamine hydrochloride, and finally add 0.2g of lithium nitrate and react for 24 hours. Collect the composite material, wash it with deionized water and ethanol in multiple stages, and dry the sample in an oven at 60°C. After drying, the nanomaterial is heated to 550°C at a rate of 2°C / min, calcined in a nitrogen atmosphere for 2h, and finally washed with water and dried to obtain Si@C. Its SEM picture is as follows Fig.13 As shown, it can be seen from the figure that it is a spherical structure gathered together.

[0121] Example 8 (for comparison)

[0122] A method for preparing three-dimensional porous silicon@carbon using lithium carbonate as a template and a lithium supplementing agent comprises the following steps:

[0123] 1) The preparation of the precursor is the same as in Example 1;

[0124] 2) The preparation of porous Si spheres is the same as in Example 1;

[0125] 3) Preparation of porous Si@C / Li2CO3:

[0126] Take 0.1g of the porous silicon spheres prepared in step 2), disperse them in 50mL of deionized water, and ultrasonicate for 10min; under magnetic stirring, add 1.21g of tris(hydroxymethyl)aminomethane) to the solution; then adjust the pH to 8.5 with hydrochloric acid solution, continue to add 60mg of dopamine hydrochloride, and finally add 0.2g of lithium carbonate and react for 24h. Collect the composite material, wash it with deionized water and ethanol in multiple stages, and dry the sample in an oven at 60°C. The dried nanomaterial is calcined at 550°C in a nitrogen atmosphere for 2h with a heating rate of 2°C / min. Finally, it is washed with water and dried to obtain porous Si@C / Li2CO3. Its TEM image is shown as follows Fig.14 As shown, it can be seen that the carbon layer on the surface of the silicon particles is not obvious.

[0127] Example 9 (for comparison)

[0128] A method for preparing three-dimensional porous silicon@carbon using lithium chloride as a template and a lithium supplementing agent comprises the following steps:

[0129] 1) The preparation of the precursor is the same as in Example 1;

[0130] 2) The preparation of porous Si spheres is the same as in Example 1;

[0131] 3) Preparation of porous Si@C / LiCl

[0132] Take 0.1 g of the porous silicon spheres prepared in step 2), disperse them in 50 mL of deionized water, and ultrasonicate for 10 minutes; under magnetic stirring, add 1.21 g of tris(hydroxymethyl)aminomethane) to the solution; then adjust the pH to 8.5 with hydrochloric acid solution, continue to add 60 mg of dopamine hydrochloride, and finally add 0.2 g of lithium chloride and react for 24 hours. Collect the composite material, wash it with deionized water and ethanol in multiple stages, and dry the sample in an oven at 60°C. The dried nanomaterial is calcined at 550°C in a nitrogen atmosphere for 2 hours with a heating rate of 2°C / min. Finally, it is washed with water and dried to obtain porous Si@C / LiCl. Its TEM image is shown as follows Fig.15 As shown, it can be seen that the surface carbon layer is not obvious.

[0133] Example 10 (for comparison)

[0134] 1) The preparation of the precursor is the same as in Example 1;

[0135] 2) The preparation of porous Si spheres is the same as in Example 1;

[0136] 3) Preparation of porous Si@C-0.6

[0137] Take 0.1 g of the porous silicon spheres prepared in step 2), disperse them in 50 mL of deionized water, and ultrasonicate for 10 minutes; under magnetic stirring, add 1.21 g of tris(hydroxymethyl)aminomethane) to the solution; then adjust the pH to 8.5 with hydrochloric acid solution, continue to add 60 mg of dopamine hydrochloride, and finally add 2 g of lithium nitrate and react for 24 hours. Collect the composite material, wash it with deionized water and ethanol in multiple stages, and dry the sample in an oven at 60°C. After drying, calcine at 550°C in a nitrogen atmosphere for 2 hours with a heating rate of 2°C / min. Finally, wash with water and dry to obtain porous Si@C-0.6. Its TEM image is shown below Fig.16 As shown, it can be seen that after increasing the lithium nitrate concentration, the carbon layer on the surface of the silicon particles becomes thinner.

[0138] Embodiment 11

[0139] A lithium-ion battery negative electrode is prepared using the above lithium nitrate as a template and a three-dimensional porous silicon@carbon nanosphere structure material of a lithium supplement as an active material. The specific preparation method is:

[0140] The three-dimensional porous Si@C composite material obtained in Example 1 was used as an active material and mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1. The slurry was obtained by grinding, and a film was coated on a copper foil and dried at 80°C for 20 hours to obtain a three-dimensional porous composite material. The three-dimensional porous Si@C composite material was cut into small discs to obtain a three-dimensional porous Si@C composite material as a negative electrode for a lithium-ion battery.

[0141] A lithium-ion battery was assembled in a glove box using a lithium sheet as a counter electrode and an electrolyte consisting of LiPF6 of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1.

[0142] The assembled lithium-ion battery was tested for charge and discharge performance using a Xinwei battery tester. The cycle stability test results at different current densities are shown in the following table. Figures 17 to 21 As shown, 0.1A g -1 After 100 cycles at the current density, the battery discharge capacity is 507 mAh g -1 , the average charge and discharge efficiency is maintained above 99%; 0.5A g -1 After 100 cycles at the current density, the battery discharge capacity is 105 mAh g -1 , the Coulomb efficiency remains at about 100%. When the current density is from 0.1 to 0.5A -1 , and then return to 0.1A g -1 When the battery discharge capacity is still 673mAh g -1 , indicating that it has good reversibility.

[0143] The negative electrode was prepared using the raw materials prepared in Example 2 to Example 10 in the same manner, and the battery performance was tested. Figure 22 to Figure 30 The following are the cycle performance diagrams of lithium-ion batteries using the composite materials prepared in Examples 2 to 10 as negative electrodes. -1 At the current density, the composite materials synthesized in different embodiments, the discharge specific capacities of the lithium-ion batteries assembled after 50 cycles were 247, 138, 164, 321, 400, 122, 300, 170 and 160 mAh g, respectively. -1 The performance is far lower than that of the battery prepared in Example 1, and only by using lithium nitrate can the higher battery performance of the present invention be achieved.

[0144] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a three-dimensional porous silicon@carbon nanosphere structure material using lithium nitrate as a template and a lithium supplement, characterized in that: The preparation method comprises the following steps: 1) Under magnetic stirring, porous Si nanospheres and tris(hydroxymethyl)aminomethane are dispersed in water, and the pH is adjusted with hydrochloric acid solution, dopamine hydrochloride is continuously added, and finally lithium nitrate is added for reaction; 2) calcining the product of step 1) in a protective atmosphere, washing and drying, and obtaining a three-dimensional porous Si@C nanosphere structure material.

2. The preparation method according to claim 1, characterized in that: In step 1), the amount ratio of porous Si nanospheres to water is 0.001-0.004 g / mL; the amount ratio of tris(hydroxymethyl)aminomethane to water is 0.15-0.25 mol / L; the amount ratio of dopamine hydrochloride to water is 0.005-0.007 mol / L; and the pH of the hydrochloric acid solution is adjusted to 8-9.

3. The preparation method according to claim 1, characterized in that: In step 1), the usage ratio of lithium nitrate to water is 0.05-0.07 mol / L.

4. The preparation method according to claim 1, characterized in that: In step 1), the reaction time is 20-30 hours.

5. The preparation method according to claim 1, characterized in that: The preparation method of porous Si nanospheres in step 1) is: 1-1) ethanol, deionized water and ammonia water are mixed, stirred, tetraethyl silicate is added dropwise, stirring is continued, the mixture is allowed to stand, the product is centrifuged and washed, and dried to obtain SiO2; 1-2) SiO2, Mg powder and NaCl are mixed and ground, and then calcined. After the calcination, they are soaked in HCl solution, washed alternately with HCl solution and deionized water, and dried to obtain porous Si balls.

6. The preparation method according to claim 5, characterized in that: In step 1-1), the volume ratio of the ethanol, ammonia water, tetraethyl silicate and deionized water is 9:1.5:1:3 to 130:3.5:3:

21.

7. The preparation method according to claim 5 or 6, characterized in that: In step 1-2), the mass ratio of SiO2, Mg powder and NaCl is 1:1:10 to 1:1.2:

30.

8. A three-dimensional porous silicon@carbon nanosphere structure material prepared by the preparation method according to any one of claims 1 to 7 using lithium nitrate as a template and lithium supplement, with a size of 200 to 500 nm, a core of porous Si, a shell of a carbon layer, and pore sizes distributed in the core and the shell.

9. A negative electrode for a lithium ion battery, characterized in that: The three-dimensional porous silicon@carbon nanosphere structure material according to claim 8 is used as the active material for preparation.

10. A lithium ion battery, characterized in that: The negative electrode of the lithium-ion battery is prepared using the negative electrode of claim 9.

Citation Information

Patent Citations

  • Silver-particle-doped silicon carbon negative electrode material preparation method

    CN108336311A

  • Preparation method of silicon-based anode material for lithium ion battery

    CN105226260A

  • Pre-lithiated silicon monoxide / carbon composite material, and preparation method and application thereof

    CN112289999A

  • Carbon-silicon composite structures and methods of fabricating thereof

    US20240128441A1

  • Process for Depositing and Prelithiating an Anode Active Material in Porous Conductive Particles for Lithium Batteries

    US20240204163A1

Cited By

  • High-power artificial graphite as well as preparation method and application thereof

    CN119976824A